Risk factors and outcomes of upper gastrointestinal bleeding in hospitalized patients in a tertiary care hospital - Essani, Zahabia Muhammad Sohail; Naeem, Filza; Om Parkash, (Journal of the Pakistan Medical Association, 2024)
Objective: To determine different aetiologies and outcomes of upper gastrointestinal bleeding in hospitalised patients. Method: The retrospective cohort study was conducted at the Aga Khan University Hospital, Karachi, and comprised data from December 2019 to April 2021 related to adult patients of either gender with non-gastrointestinal illnesses who developed bleeding at least 24 hours after admission. Data was reviewed for clinical characteristics, cause of bleeding and clinical outcome. Data was analysed using SPSS 23. Results: Among 47,337 hospitalised patients, upper gastrointestinal bleeding was identified in 147(0.3%); 98 (66.7%) males and 49 (33.3%) females. The overall mean age was 62.73±14.81 years (range 20-95 years). Of the total, 125(85%) presented with overt bleeding and 22(15%) with a drop in haemoglobin level. There were 34(23%) patients on aspirin, 36(24%) on dual anti-platelets, 41(28%) on therapeutic anticoagulation, and 81(55%) on prophylactic anticoagulation. There were 7(5%) patients having a history of non-steroidal anti-inflammatory drugs (NSAIDs), and 12(8%) were on steroids. In terms of associated medical conditions, pneumonia, stroke, and acute coronary syndrome were commonly seen with frequency of 29.9%, 8.1% and 7.4% respectively. Overall, 36(24.4%) patients underwent endoscopy, 8(5.4%) had therapeutic measures to control bleeding, 14(9.5%) had bleeding for >48 hours, 89(60.5%) were stepped up to special care. Mortality was seen in 36(24.5%) cases. Conclusion: Hospital acquired gastrointestinal bleeding was found to be uncommon, and there were several risk factors for such bleeding events. Key Words: Gastrointestinal haemorrhage, Melena, Hematemesis.